Effect of Red Wine Consumption on Serum Oxidation and Adiponectin Levels in Overweight and Healthy Individuals - Karadeniz Muammer; Akçay Yasemin D.; Yıldırım Hatice K.; Yılmaz Candeğer; Sözmen Eser Y. (Polish Journal of Food and Nutrition Sciences)
Obesity is a well-known independent risk factor for CVD and metabolic syndrome. It has been shown that moderate red wine consumption might reduce the risk of cardiovascular disease (CVD). The aim of this study was to investigate whether red wine has anti-inflammatory and antioxidative effect in overweight subjects.